THE IMPACT OF FIA’S 2022 RULE CHANGES ON COMPETITIVE BALANCE IN FORMULA 1 - Prince, Cameron Scott (East Carolina University, 2023)
In 2022, the Fédération Internationale de l'Automobile (FIA) implemented a number of rule changes regarding car design to promote closer racing in Formula 1. This study constructs a balanced sample of race lap times from the 2021 (pre) and 2022 (post) seasons to investigate the impact of these rule changes on competitive balance. After controlling for driver, track, and lap fixed-effects, results from recentered influence function regressions suggest that the 2022 regulations improved competitive balance in Formula 1 racing. Specifically, we estimate that the standard deviation and Gini coefficient for lap times declined by 8.8% and 6.8%, respectively. These results are driven by increases in lap times below the 95th percentile and decreases in lap times above the 95th percentile (the slowest cars) in the 2022 season. The Lorenz curve for lap times shifts up significantly in 2022 (after the rule changes), except for the bottom quintile (the fastest 20% of lap times), where we find no statistically distinguishable change in the share of overall lap times. Collectively, these results suggest that the estimated improvements in competitive balance in 2022 are being driven by closer racing among drivers outside of the fastest two deciles.
Keywords: Formula 1, competitive balance